PENGARUH KUALITAS PELAYANAN TERHADAP KEPUASAN KONSUMEN ARFA BARBERSHOP DI SURAKARTA - Rahayu Triastity, Farizky Yudiatma & (Universitas Slamet Riyadi, 2015)
Purpose of this research to analyze effect of tangibles, reliability, responsiveness, assurance and empathy on customer satisfaction. Research design was survey on customer of Arfa Barbershop Surakarta. Type of data used qualitative and quantitative data. Source of data used primary and secondary data. Population are customers Arfa Barbershop Surakarta. Sample used 100 customer with convenience sampling. Technique of collecting data used questionnaire, observation and documentation. Analysis data used assumption classic test, multiple regression, t test, F test and coefficient determination. Result showed that tangibles has did not significant effect on customer satisfaction. Reliability has significant effect on customer satisfaction. Responsiveness has significant effect on customer satisfaction. Assurance has did not significant effect on customer satisfaction. Empathy has significant effect customer satisfaction. Reliability was a dominant variable on customer satisfaction because has value of coefficient regression are biggest. Keywords: tangibles, reliability, responsiveness, assurance, empathy and customer satisfaction.